Characterization and comparative evaluation of two atmospheric plasma sources for water treatment. Issue 3 (15th December 2017) - Bosi, Franco J.; Tampieri, Francesco; Marotta, Ester; Bertani, Roberta; Pavarin, Daniele; Paradisi, Cristina
Abstract : A reactor with two interchangeable plasma sources was developed and tested in water decontamination experiments using phenol as model organic pollutant. The two configurations were characterized and compared by determining the reactive species produced in the aqueous phase (concentration of ozone and of hydrogen peroxide as a function of input energy and rate of OH radical production) and the efficiency in phenol degradation. The streamer discharge performed significantly better than the dielectric barrier discharge: the rate of OH radicals production was ten times faster and the efficiency of phenol degradation, as measured by the G 50 parameter, was more than twice as large. Moreover, the streamer discharge induced process was kinetically faster and achieved better mineralization yields in shorter times. Abstract : A new atmospheric plasma reactor for water treatment is developed and tested, with two interchangeable electrode configurations to implement DBD or streamer regimes. The performance is evaluated in terms of production of reactive species (O3, H2 O2, and OH radicals) and by monitoring the degradation of phenol, a model organic pollutant, and its mineralization to CO2 .